2023
DOI: 10.4103/jos.jos_34_22
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Brodie bite in untreated orthodontic patients in Nigeria

Abstract: OBJECTIVE: The Brodie bite (BRB) is a rare posterior crossbite affecting the transverse occlusal relationship with the palatal cusps of the upper molars, biting into the vestibule and outside the buccal cusps of the lower molar teeth. The BRB is a highly challenging orthodontic problem and is an extreme form of scissors bite. Patients with this problem present with facial deformity and inability to chew on the affected side. The problem is usually not identified until it becomes severe. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The prevalence of Brodie's bite is from 0.5 to 2.3 %. The prevalence of scissor bite is from 0.5 to 5.9 % [18]. Data from the examination of children in one of the regions of Saudi Arabia showed that more than half of the examinees had Class I malocclusion (anterior crossbite, posterior crossbite, open bite, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of Brodie's bite is from 0.5 to 2.3 %. The prevalence of scissor bite is from 0.5 to 5.9 % [18]. Data from the examination of children in one of the regions of Saudi Arabia showed that more than half of the examinees had Class I malocclusion (anterior crossbite, posterior crossbite, open bite, etc.).…”
Section: Introductionmentioning
confidence: 99%